"I Think the Temperature was 110 Degrees!": Work Safety Discussions Among Hispanic Farmworkers. Issue 1 (2nd January 2019) - Luque, John S.; Bossak, Brian H.; Davila, Caroline B.; Tovar-Aguilar, Jose Antonio
ABSTRACT: Heat-related illness (HRI) among migrant and seasonal farmworkers is an occupational risk addressed through varying mitigation strategies by individual workers and supervisors. The purpose of this pilot study was to describe farmworkers' experience with HRI prevention strategies and assess HRI information seeking preferences, especially the feasibility of using mobile phone apps to access this information. Five focus groups were administered to Hispanic farmworkers in South Carolina. Questions included the following topics: health information seeking preferences; farmworkers' perceptions of occupational risks; coping strategies; past experiences with HRIs; water, rest, and shade practices; access to health care; and any employer-provided training received. There was consensus across the groups that the workers at highest risk for HRIs were either inexperienced or new workers in the fields. Farmworkers ascribed responsibility for one's well-being while working in the heat more as an individual factor than as an employer's responsibility. Farmworkers received training on the OSHA Heat Safety Tool app and provided positive feedback about the educational content and temperature information warnings. These findings suggest the potential for supervisors to take a more active role in heat safety education using mobile technology.